Frequency of HIV testing among gay and bisexual men in the UK: implications for HIV prevention. Issue 9 (15th March 2016) - McDaid, LM; Aghaizu, A; Frankis, J; Riddell, J; Nardone, A; Mercey, D; Johnson, AM; Hart, GJ; Flowers, P
Abstract : Objectives: The aim of the study was to explore HIV testing frequency among UK men who have sex with men (MSM) in order to direct intervention development. Methods: Cross‐sectional surveys were completed by 2409 MSM in Edinburgh, Glasgow and London in 2011 and a Scotland‐wide online survey was carried out in 2012/13. The frequency of HIV testing in the last 2 years was measured. Results: Overall, 21.2% of respondents reported at least four HIV tests and 33.7% reported two or three tests in the last 2 years, so we estimate that 54.9% test annually. Men reporting at least four HIV tests were younger and less likely to be surveyed in London. They were more likely to report higher numbers of sexual and anal intercourse partners, but not "higher risk" unprotected anal intercourse (UAI) with at least two partners, casual partners and/or unknown/discordant status partners in the previous 12 months. Only 26.7% (238 of 893) of men reporting higher risk UAI reported at least four tests. Among all testers ( n = 2009), 56.7% tested as part of a regular sexual health check and 35.5% tested following a risk event. Differences were observed between surveys, and those testing in response to a risk event were more likely to report higher risk UAI. Conclusions: Guidelines recommend that all MSM test annually and those at "higher risk" test more frequently, but our findings suggest neither recommendation is being met. Additional efforts are required to increase testing frequency and harness the opportunities provided by biomedical HIV prevention. Regional, demographic and behavioural differences and variations in the risk profiles of testers suggest that it is unlikely that a "one size fits all" approach to increasing the frequency of testing will be successful.